On the Ergodic Theory of Free Group Actions by Real-Analytic Circle Diffeomorphisms - Navas-Flores, A (Springer New York LLC, 2018)
We consider finitely generated groups of real-analytic circle diffeomorphisms. We show that if such a group admits an exceptional minimal set (i.e., a minimal invariant Cantor set), then its Lebesgue measure is zero; moreover, there are only finitely many orbits of connected components of its complement. For the case of minimal actions, we show that if the underlying group is (algebraically) free, then the action is ergodic with respect to the Lebesgue measure. This provides first answers to questions due to É. Ghys, G. Hector and D. Sullivan. © 2017, Springer-Verlag GmbH Germany, part of Springer Nature.